System design of a two wheeler self balanced vehicle - Rumi, Sheikh Mohibul Islam; Islam, I.S.M. Shanamul; Hossain, Mehdi Fakid (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.